Cisplatin treatment of C6 rat glioma in vivo did not influence copy number alterations and growth pattern of tumor-derived resistant cells - Stepanenko, A.A.; Baklaushev, V.P.; Vassetzky, Y.S.; Dmitrenko, V.V. (Вiopolymers and Cell, 2015)
Aim. To investigate whether the cisplatin treatment of C6 rat glioma in vivo impacts the copy number alterations (CNAs), proliferation and colony formation efficiency (CFE) of tumor-derived cisplatin-resistant cells. Methods. The glioma modeling was performed by means of intracerebral stereotactic implantation of rat glioma C6 cells into the striatum region of rats. The rats received 20 % dimethyl sulfoxide DMSO (C6R1) or cisplatin (C6R4CIS and C6R5CIS) injected intraperitoneally (5 mg/kg) three times per week. After 10 injections, gliomas were resected and the cells were cultured for in vitro analysis. CNAs were analyzed by array comparative genome hybridization, proliferation by direct cell counting in hemocytometer, CFE by soft agar assay. Results. No significant changes in the CNAs and CFE of cisplatin-treated rat glioma C6R4CIS and C6R5CIS cell lines were observed compared to the vehicle-treated control C6R1 cells. However, C6R5CIS but not C6R4CIS had a reduced proliferation. Interestingly, both cisplatin- and vehicle-treated brain-grown cells had a reduced proliferation and CFE in comparison to the parental C6 cells. Conclusions. Despite numerous reports on the destabilizing effects of cisplatin on genome and phenotype, the cisplatin treatment of C6 cells in vivo did not affect genome stability, CFE, and had an inconsistent effect on the proliferation in vitro. The rat brain microenvironment may potentially impact the growth characteristics of rat glioma cells. Мета. Перевірити, чи впливає терапія цисплатином клітин С6 гліоми щура in vivo на зміни числа копій хромосомних локусів, проліферацію і ефективність формування колоній цисплатин-нечутливими клітинами. Методи. Моделювання гліоми було виконано за допомогою внутрішньомозкової стереотаксичної імплантації щурячих клітин гліоми С6 в область смугастого тіла щура. Щурам вводили внутрішньоочеревинно 20 % ДМСО (C6R1) або 5 мг/кг цисплатин (C6R4CIS і C6R5CIS) три рази на тиждень. Після 10 ін’єкцій, клітини гліоми були вилучені і поміщені в ростове середовище для подальшого аналізу in vitro. Зміни кількості копій хромосомних локусів було проаналізовано за допомогою порівняльної геномної гібридизації, аналіз проліферації здійснювали прямим підрахунком клітин в гемоцитометрі, а ефективність формування колоній (ЕФК) – аналізом росту в м’якому агарі. Результати. Ніяких істотних змін числа копій хромосомних локусів, проліферації та ЕФК між лініями C6R4CIS, C6R5CIS і C6R1 не спостерігалося. Однак C6R5CIS, але не C6R4CIS лінія знизила проліферацію при порівнянні з C6R1. Цікаво, що клітинні лінії C6R4CIS, C6R5CIS і C6R1 мають нижчий рівень проліферації та ЕФК при порівнянні з вихідною батьківською лінією C6. Висновки. Незважаючи на численні повідомлення про дестабілізуючий вплив цисплатину на геном і фенотип клітин, терапія цисплатином С6 гліоми щура in vivo не вплинула на геномну стійкість, ЕФК та мало суперечний вплив на проліферацію клітин in vitro. Мікрооточення щурячого мозку потенційно може впливати на ростові характеристики пухлинних клітин гліоми. Цель. Проверить, влияет ли терапия цисплатином С6 глиомы крысы in vivo на изменения числа копий хромосомных локусов, пролиферацию и эффективность образования колоний цисплатин-нечувствительными клетками. Методы. Моделирование глиомы было выполнено с помощью стереотаксической имплантации аллогенных крысиных клеток глиомы С6 в область каудопутамена. Крысам с экспериментальной глиомой вводили внутрибрюшинно 20 % ДМСО (C6R1) или 5 мг/кг цисплатин (C6R4CIS и C6R5CIS) три раза в неделю. После 10 инъекций, клетки глиомы были изъяты и помещены в ростовую среду для дальнейшего анализа in vitro. Изменение числа копий хромосомных локусов было проанализировано с помощью сравнительной геномной гибридизации, анализ пролиферации осуществляли прямым подсчетом клеток в гемоцитометре, а эффективность образования колоний (ЭОК) – анализом роста в мягком агаре. Результаты. Никаких существенных изменений числа копий хромосомных локусов и ЭОК между линиями C6R4CIS, C6R5CIS и C6R1 не наблюдалось. Однако C6R5CIS, но не C6R4CIS линия снизила пролиферацию при сравнении с C6R1. Интересно, что клеточные линии C6R4CIS, C6R5CIS5 и C6R1 имеют более низкий уровень пролиферации и ЭОК, чем исходная родительская линия C6. Выводы. Несмотря на многочисленные сообщения о дестабилизирующем влиянии цисплатина на геном и фенотипи клеток, терапия цисплатином С6 глиомы крысы in vivo не повлияла на геномную устойчивость, ЭОК и оказывала противоречивое действие на пролиферацию in vitro. Микроокружение крысиного мозга потенциально может влиять на ростовые характеристики опухолевых клеток глиомы.